SYNGAP1 and Methylenetetrahydrofolate in Cerebrospinal Fluid: Cognitive Development after Oral Folate (5-Methyltetrahydrofolate) Supplementation in a 5-Year-Old Girl - Hess, Valentin; Miguel, Justine; Bonnemains, Chrystèle; Bilbault, Claire (Journal of Pediatric Neurology, 2021)
Synaptic Ras GTPase-activating protein 1 (SYNGAP1), also called Ras-GAP 1 or RASA5, is a cerebral protein with a role in brain synaptic function. Its expression affects the development, structure, function, and plasticity of neurons. Mutations in the gene cause a neurodevelopment disorder termed mental retardation-type 5, also called SYNGAP1 syndrome. This syndrome can cause many neurological symptoms including pharmaco-resistant epilepsy, intellectual disability, language delay, and autism spectrum disorder. The syndrome naturally evolves as epileptic encephalopathy with handicap and low intellectual level. A treatment to control epilepsy, limit any decrease in social capacities, and improve intellectual development is really a challenging goal for these patients. The etiologic investigation performed in a 5-year-old girl with early epileptic absence seizures (onset at 6 months) and psychomotor delay (language) revealed a low methylenetetrahydrofolate level in cerebrospinal fluid in a lumbar puncture, confirmed by a second one (35 nmol/L and 50 nmol/L vs. 60–100 nmol/L normal), associated with normal blood and erythrocyte folate levels. Hyperhomocysteinemia, de vivo disease, and other metabolic syndromes were excluded by metabolic analysis. No genetic disorders (like methylenetetrahydrofolate reductase and methenyltetrahydrofolate synthetase) with folate metabolism were found. The physical examination showed only a minor kinetic ataxia. An oral folate (5-methyltetrahydrofolate) supplementation was started with oral vitamin therapy. The child showed good progress in language with this new treatment; epilepsy was well balanced with only one antiepileptic drug. The SYNGAP1 mutation was identified in this patient's genetic analysis. Since the start of folate supplementation/vitamin therapy, the patient's neurologic development has improved. To our knowledge, no association between these two pathologies has been linked and no patient with this SYNGAP1 mutation has ever showed much intellectual progress. Low cerebral methylenetetrahydrofolate levels could be associated with SYNGAP1 mutations. One of the hypotheses is the link of folate metabolism with epigenetic changes including methylation process. One inborn metabolic activity in folate metabolism may be associated with SYNGAP1 disease with epigenetic repercussions. Further studies should assess the link of SYNGAP1 and methyltetrahydrofolate and the evolution of SYNGAP1 patients with oral folate supplementation or vitamin therapy.
Keywords: pediatric neurology; SYNGAP1; 5MTHF; neurotransmitters; vitamin therapy